Povos indígenas em isolamento voluntário na Amazônia brasileira: o sexto século de genocídios e diásporas indígenas - Silva, Rodolfo Ilário da (Universidade de Brasília, 2017)
According to the United Nations and the Organization of American States there are approximately 200 indigenous groups living in isolation or recent contact (PIIRC) in South America. In Brazil, the government recognizes 103 groups in isolation and 18 groups in recent contact. From a macro-historical perspective, the main objective is to identify how the contemporary situation of these peoples is related to the political, territorial and economic expansion dynamics of the colonization and internal colonialism processes in Brazil. Our hypothesis is that this situation can be described as the sixth century of indigenous genocides and diasporas, due to the continuity of practices of violence, territorial usurpations and violations of the rights of indigenous peoples, besides the processes of systematic run away imposed to the groups that refuse to maintain relations with the surrounding society. Both processes of genocide and diaspora began with colonization, were succeeded by internal colonialism, and they currently persist through the appropriation of Amazonian resources and territories to be incorporated into the national and global markets. Therefore, this chronological dimension does not represent an absolute and linear process, but dynamics with varying intensities over time, shifts of the historical agents involved, but which have not been abolished. It is also not a way to promote a historical victimization of indigenous peoples, since diasporas and voluntary isolation are indigenous strategies of resistance and pursuit for self-determination.